Damage protection of earthquake resistant structures by means of damped braces. (October 2021) - Mazza, Fabio
Highlights: Effects of previous earthquakes on the retrofitting of framed buildings is studied. A degrading plastic-damage model is proposed as function of a damage index. A displacement-damage-based design (DDBD) procedure of HYDBs is proposed. A computer-aided software DAMPERS is implemented to automate the DDBD procedure. Nonlinear seismic analysis of an archetype building is carried out. Abstract: Supplementary energy dissipation is an efficient technique for the retrofitting of as built framed buildings as long as the loss of capacity due to previous seismic degradation is evaluated properly. Most of the displacement-based design procedure of damped braces only considers the capacity curve of an initially undamaged structure, while the hysteretic energy is accounted for by an equivalent viscous damping. However, structures may be initially damaged by previous earthquakes, so the proportioning of the damped braces should include the effects of the cumulative damage caused by previous loading cycles. A displacement-damage-based design procedure is proposed and implemented by means of a computer-aided tool named DAMPERS (DAMage Protection of Earthquake Resistant Structures). The residual capacity that a building might experience when subjected to more than one earthquake during its nominal life is taken into account. The loss of capacity of the original structure is evaluated by a combined plastic-damage model, obtained as an in-parallel combination of elastic-perfectly plastic and elastic-softening damage mechanisms, and a damage index, accounting for the cyclic damage of each pair of mechanisms. An archetype six-storey reinforced concrete framed building, representative of the Italian residential housing stock constructed during the 1990s, is retrofitted with hysteretic damped braces designed assuming different damage evolution laws during previous earthquakes. Three configurations of masonry infills (MIs) are considered: bare frame, with nonstructural MIs; infilled frame, with a uniform in-elevation distribution of structural MIs; pilotis frame, with no MIs at the ground floor and structural MIs at the other floors. OpenSees is the computational platform for the nonlinear seismic analysis of the unbraced and damped braced structures, with reference to records scaled in line with the hypotheses adopted and considering failure modes of structural and nonstructural elements.